Botulinum toxin as an adjunctive therapeutic option in sleep Bruxism: A narrative literature review (Research, Society and Development, 2025)
Botulinum toxin has emerged as an adjunctive therapeutic option for the treatment of sleep bruxism, a condition characterized by the involuntary grinding or clenching of teeth during sleep. This review aims to explore the efficacy and safety of botulinum toxin as an adjunctive therapeutic option in the management of sleep bruxism. Recent studies indicate that when injected into the masticatory muscles, botulinum toxin can reduce excessive muscle activity, providing symptom relief and preventing dental wear. This treatment works by blocking the release of acetylcholine at neuromuscular junctions, thereby reducing muscle contractions. The efficacy and safety of botulinum toxin for sleep bruxism have been supported by various studies, highlighting it as a viable alternative, particularly for patients who do not respond well to other forms of treatment, such as occlusal splints or behavioral therapies. However, a thorough assessment of the risks and benefits is essential, as well as considering the need for complementary treatments to optimize results and minimize potential side effects.